Software Testing and Continuous Quality Improvement, Second Edition - Lewis, William (CRC Press, 2009)
Software Testing and Continuous Quality Improvement, Second Edition, illustrates a quality framework for software testing in traditional structured and unstructured environments. It explains how a continuous quality improvement approach promotes effective testing, and it analyzes the various testing tools and techniques that you can choose.